2011
DOI: 10.1101/gr.133645.111
|View full text |Cite
|
Sign up to set email alerts
|

A transforming KIF5B and RET gene fusion in lung adenocarcinoma revealed from whole-genome and transcriptome sequencing

Abstract: The identification of the molecular events that drive cancer transformation is essential to the development of targeted agents that improve the clinical outcome of lung cancer. Many studies have reported genomic driver mutations in non-small-cell lung cancers (NSCLCs) over the past decade; however, the molecular pathogenesis of >40% of NSCLCs is still unknown. To identify new molecular targets in NSCLCs, we performed the combined analysis of massively parallel whole-genome and transcriptome sequencing for canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
347
1
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 437 publications
(359 citation statements)
references
References 42 publications
10
347
1
1
Order By: Relevance
“…To date, several cancer genome sequencing studies have discovered RET fusions in B1-2% of lung cancer. [10][11][12][13] RET fusions were the potential therapeutic targets of multitargeted kinase inhibitors, vandetanib, sunitinib, and sorafenib. [11][12][13] Importantly, RET rearrangement is mutually exclusive with aberrations in EGFR, KRAS, ALK, HER2, and BRAF in lung cancer.…”
mentioning
confidence: 99%
“…To date, several cancer genome sequencing studies have discovered RET fusions in B1-2% of lung cancer. [10][11][12][13] RET fusions were the potential therapeutic targets of multitargeted kinase inhibitors, vandetanib, sunitinib, and sorafenib. [11][12][13] Importantly, RET rearrangement is mutually exclusive with aberrations in EGFR, KRAS, ALK, HER2, and BRAF in lung cancer.…”
mentioning
confidence: 99%
“…Germline and somatic gain-of-function RET mutations are known to predispose to multiple endocrine neoplasia type 2 and sporadic medullary thyroid cancer, respectively, whereas somatic RET gene fusions account for the majority of radiation-induced and sporadic papillary thyroid cancers. In 2011, investigators from Seoul identified a fusion gene involving RET partnered with KIF5B in a young never smoker with lung adenocarcinoma (42). RET rearrangements have since been identified in approximately 1 to 2% of patients with adenocarcinoma or adenosquamous carcinoma of the lung.…”
Section: Ret Fusionsmentioning
confidence: 99%
“…RET means that it will "rearrange during transfection"; the DNA of RET was first discovered rearranged in a 3T3 fibroblast cell line and transfection took place after it. Recently, RET rearrangements were discovered in NSCLC by using different screening strategies from cancer and normal tissue which originated from a lung cancer patient, in whom there were no driver mutation or fusion, who had no smoking history, and whose family has no tumor history [53]. KIF5B is a new chimeric fusion transcript, which was originally discovered as a new driver mutation in NSCLC by four independent research groups simultaneously.…”
Section: Retmentioning
confidence: 99%